Modern tendencies of studying subjective well-being of personality in adolescent and youth - Khaleeva Аnna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The article defines terms on mental health and emotional well-being of adolescents and adolescents, and outlines major trends in mental health and emotional well-being of young people over the past decades. The aim of the article is to highlight and establish the importance of emotional and subjective well-being in adolescence and youth, to identify their further influence on the formation of the personality and its full life. Adolescence is seen as a critical period of development with long-term effects on the health and well-being of the individual. It is stated that the central factor in the health and well-being of adolescents is the interaction of young people with their environment, with people and attitudes in their daily lives. The most important determinants of adolescents’ health are in their environment, as well as the choices and opportunities for improving the health or adverse behaviors of today’s society. Factors that influence on the subjective and emotional well-being (sleep deprivation, increased stress, social relationships, the impact of violence) have been taken into account. The components and characteristics that support emotional and subjective well-being are identified, such as: self-esteem, motivation, stability, self-efficacy, hope and optimism, while high levels of anxiety, depression and stress can interfere with emotional health and well-being. In determining the factors that affect the emotional and subjective well-being of adolescents and youths, it is important to take into account the multidimensional nature of well-being and what sources and factors form it. The main sources affecting the sense of self and overall well-being of a person in adolescence and youth are family, community, peers, school environment and teachers. The modern world and the environment of human development are constantly changing, which has a significant impact on the well-being of the individual and its further development. Such changes are important elements for the continued successful interaction of adolescents and young people and their integration in society.